OTENTISITAS HADITS CARA SUJUD TANGAN DAHULU - MZ, Zainuddin (Universitas Islam Madura, 2015)
This article will also be more focussed by study of hadits which have been studied by ceremony of Nadwah Mudzakarah which presents hadits. It is way of motion for sujud by prioritize hand assessed by dhaif (weak). Thereby, it is expected by people who get hold assuring for its deed of him. Beforehand, need of methodologies clarified determine status of deliverer of hadits if which is pertinent to be assessed by al-jarh (negative) meanwhile he is also assessed by al-ta'dil (positive). this study of writer relate to go down good bestowing (sujud) of first opinion and also second weakening weight, hence temporarily we decide when going down we may not put down hand in advance from knee or on the contrary, its meaning, no way special which we must do. It seems, this fatwah submitted because Nadwah fail to look for manual which is shahih, but why giving sect solution of al-tanwi' or hiyar. We may select; choose between two opinions in front. Though this competent solution on the market predict all real correct manuals or shahih. Like parallel hands up until shoulder or lifted higher a little. In problem of religious service more than anything else religious service of tauqifiyah bargain which is competent to be given its prohibition without existence of unvalidible.